Afazja jako zaburzenie mowy po urazie mózgu – studium przypadku - Lewicka, Tatiana (Logopedia Silesiana, 2012)
Speech disorder after brain damages in aphasia – case study Cranial-cerebral traumas are a serious sociomedical issue. Brain damages, caused by experienced injury, often lead to various kinesthetic deficits, as well as to cognitive and language disorders. Due to the damage of a nervous system, there are many deep speech disorders such as aphasia, mainly senso-motorical type. The right evaluation of the appearing deficits, the right definition of therapeutical objectives and implementing of the therapy can give brain trauma patients the chance to regain the possibility to communicate.